The small GTPase, nucleolar GTP-binding protein 1 (NOG1), has a novel role in plant innate immunity - Seonghee Lee (Nature Portfolio, 2017)
Abstract Plant defense responses at stomata and apoplast are the most important early events during plant-bacteria interactions. The key components for the signaling of stomatal defense and nonhost resistance have not been fully characterized. Here we report the newly identified small GTPase, Nucleolar GTP-binding protein 1 (NOG1), functions for plant immunity against bacterial pathogens. Virus-induced gene silencing of NOG1 compromised nonhost resistance in N. benthamiana and tomato. Comparative genomic analysis showed that two NOG1 copies are present in all known plant species: NOG1-1 and NOG1-2. Gene downregulation and overexpression studies of NOG1-1 and NOG1-2 in Arabidopsis revealed the novel function of these genes in nonhost resistance and stomatal defense against bacterial pathogens, respectively. Specially, NOG1-2 regulates guard cell signaling in response to biotic and abiotic stimuli through jasmonic acid (JA)- and abscisic acid (ABA)-mediated pathways. The results here provide valuable information on the new functional role of small GTPase, NOG1, in guard cell signaling and early plant defense in response to bacterial pathogens.